Evaluation of diagnostic techniques for the determination of trichomonas vaginalis infection in two selected groups of females - Banneheke, B.M.H.A (My University, 2009)
Trichomoniasis is the most common non viral sexually transmitted disease in the world and is considered as an orphan in the field of medicine being under diagnosed and under treated by the medical community. The World Health Organization estimates that the global incidence of 174 million cases per year. 44 percent (76.5 million) of cases occur in the South and South East Asia. Vaginal trichomoniasis has been linked with complications such as pre term birth. pre mature rupture of membranes. low birth weight. post-abortion or posthysterectomy infection and acquisition and transmission of HIV. (Madico et af .. 1998: Wendel. 2003: Schwebke and Burgess. 2004; Schwebke. 2004). Trichomonas vagina lis is a predictor for cervical neoplasia (Viikki et af .. 2000). T. vagina/is can reduce the chances of conception for both female and mates (Soper. 2004). The objective of this study was to evaluate the diagnostic techniques to determine T. vaginalis infection among a group of inmates from a rehabilitation house and group of clinic patients attending gynaecology and sexually transmitted diseases clinics. Residents of the rehabilitation house had a background of being sexual workers. victims of sexual harassments, grown up children from orphanages. deserted by the family or psychiatric. Dipstick test was performed only on 100 patients and had a positivity rate of 10 percent . No positives were detected by microscopy of Gram stained dry smears. Out of the 29 that were positive by laboratory tests. 11 were in the age group of 36-45 years and 9 each in the other two age groups (1525 and 26-35 years). The majority of infected patients were married. Most of the females that were positive (86.2 Percent ) had I to 4 pregnancies. There was no statistically significant relationship between the presence of symptoms and trichomoniasis. Although not significant 82.7 percent of positives had a pH value between 6-8. Sensitivity and specificity of direct microscopy of vaginal smear. urine sediment and dipstick was 68 percent and 100 percent . 48 percent and 100 percent and 96 percent respectively when compared with culture. No metronidazole resistance was detected among our study population. Only 46.2 percent consented to obtain SOL YSs indicating the low acceptability of SOL YS. We also observed that SOL YSs were comparable to vaginal swabs collected by the clinicians